PENGEMBANGAN MEDIA DIGITAL E-STORY BOOK TEMA GOTONG ROYONG UNTUK SISWA KELAS 5 SEKOLAH DASAR - Anggraini, Weinty; Arafik, Muh; Rahma Kumalasari, Ardika; Rina Mahanani, Etyka; Firdaus Mashuri, Muhammad; Okta Barera, Richa; Anggraeni, Silvia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the limited use of engaging and interactive educational media in Pancasila Education lessons, which resulted in students struggling to grasp the concept of gotong royong (mutual cooperation) and showing low engagement during instruction. The study aimed to design a digital E-Story Book centered on the theme of gotong royong for fifth-grade elementary school students and to assess its validity and practicality. The research employed the Research and Development (R&D) method and the ADDIE development model, comprising the stages of analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, questionnaires, and expert validation sheets. The product underwent validation by subject matter and media experts, followed by practicality testing involving teachers and students. Validation results indicated that the media achieved a score of 85.6% from subject matter experts and 89.4% from media experts, placing it in the